2023
DOI: 10.3389/fpsyt.2023.1110525
|View full text |Cite
|
Sign up to set email alerts
|

Striatal increase of dopamine receptor 2 density in idiopathic and syndromic mouse models of autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) comprises a wide range of neurodevelopmental phenotypes united by impaired social interaction and repetitive behavior. Environmental and genetic factors are associated with the pathogenesis of ASD, while other cases are classified as idiopathic. The dopaminergic system has a profound impact in the modulation of motor and reward-motivated behaviors, and defects in dopaminergic circuits are implicated in ASD. In our study, we compare three well-established mouse models of ASD, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…However, in vitro studies indicated that PPA treatment reduced the DRD1 protein level in PC12 cells. This observed inconsistency may be attributed to different expressions of DRD1 in different ASD models (Chhabra et al, 2023; Homberg et al, 2016; Lee et al, 2018) and the potential of lotusine to target other proteins to promote DRD1 expression, such as fragile X mental retardation protein (FMRP) (Wang et al, 2008), which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro studies indicated that PPA treatment reduced the DRD1 protein level in PC12 cells. This observed inconsistency may be attributed to different expressions of DRD1 in different ASD models (Chhabra et al, 2023; Homberg et al, 2016; Lee et al, 2018) and the potential of lotusine to target other proteins to promote DRD1 expression, such as fragile X mental retardation protein (FMRP) (Wang et al, 2008), which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Gene variants associated with dopaminergic markers and receptors have been identified in ASD ( De Krom et al, 2009 ; Staal et al, 2012 ; Gangi et al, 2016 ; Mariggiò et al, 2021 ). Several ASD animal models show increased gene expression of dopamine D2 receptors in iMSNs ( Maisterrena et al, 2022 Chhabra et al, 2023 ; reviewed in Gandhi and Lee, 2021 ). Increased striatal levels of dopamine D2 receptors was documented in Rett syndrome ( Chiron et al, 1993 ) and more recently, increased striatal D2 receptor gene expression has been reported in ASD post-mortem brains ( Brandenburg et al, 2020 ).…”
Section: Dopamine Control Of Cortico-striatal Inputs and Asd Behavior...mentioning
confidence: 99%